Redescription of Orobdella ijimai (Hirudinida: Arhynchobdellida: Gastrostomobdellidae), and two new species of Orobdella from the Ryukyu Archipelago, Japan - Nakano, Takafumi (Zootaxa, 2011)
Sexannulate Orobdella leech, Orobdella ijimai, is redescribed based on newly collected specimens from the type locality, Nikko, Tochigi Pref., Japan, since this species was originally described based on limited number of characters. In addition, two new sexannulate species, Orobdella dolichopharynx sp. nov. from Amamioshima Island in the Ryukyu Archipelago, Japan, and Orobdella shimadae sp. nov. from Okinawajima Island also in the Ryukyu Archipelago, are described. They resemble O. ijimai in the annulation of mid-body somites, but they differ from the latter in the annulation of somite VIII, position of gonopores, the lack of gastropore, the length of pharynx, the shape of gastroporal duct, and the morphology of male genital organ. Two new Orobdella species differ from each other in the annulation of somite VII, the position of gonopores, and the shape of gastroporal duct. In accordance with the two new species, the diagnosis of Orobdella is slightly emended.